2019
DOI: 10.1155/2019/5256781
|View full text |Cite
|
Sign up to set email alerts
|

Schinus terebinthifoliusEssential Oil Attenuates Scopolamine-Induced Memory Deficits via Cholinergic Modulation and Antioxidant Properties in a Zebrafish Model

Abstract: Schinus terebinthifolius is a plant well recognized for its therapeutic profile such as anti-inflammatory and antitumor activities, promoting antibacterial activity and antioxidant and antidiabetic properties. This study aimed at examining whether Schinus terebinthifolius memory-enhancing activities are mediated by cholinergic and brain antioxidant systems in a scopolamine zebrafish model. Schinus terebinthifolius essential oil (10, 25, and 50 μL/L) was delivered to zebrafish by immersion in water for 8 days. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 60 publications
1
21
0
Order By: Relevance
“…SCP administration generates free radicals and damages the anti-oxidant defence mechanism by damaging the anti-oxidant enzymes [36]. This fact is well established in rodent models [37] as well as in zebrafish [38]. Our study demonstrates that even single dose of scopolamine significantly induces the generation of free radicals.…”
Section: Discussionsupporting
confidence: 61%
“…SCP administration generates free radicals and damages the anti-oxidant defence mechanism by damaging the anti-oxidant enzymes [36]. This fact is well established in rodent models [37] as well as in zebrafish [38]. Our study demonstrates that even single dose of scopolamine significantly induces the generation of free radicals.…”
Section: Discussionsupporting
confidence: 61%
“…In a previous study, Zanandrea et al [ 46 ] showed that SCOP administration (100 µM for 1 h) to zebrafish did not alter the specific activity of AChE compared to control fish. In contrast, several other reports have demonstrated that SCOP (100 µM for 30 min) increased the activity of this enzyme in the zebrafish brains [ 36 , 37 , 38 , 92 , 93 ]. Ziani et al [ 41 ] showed that NIC (1 mg/L for 3 min) increases the AChE activity when it is co-administered with a compound that provokes a fear response in zebrafish but not when NIC is administered alone.…”
Section: Resultsmentioning
confidence: 63%
“…The biochemical results obtained in this study indicated that COT and 6HLN exhibit an antioxidant profile in the SCOP-induced zebrafish model of AD. Several reports showed that SCOP treatment induces oxidative stress in the brain of zebrafish [ 36 , 37 , 38 , 92 , 93 ] or rodents [ 64 , 96 , 97 , 98 , 99 ]. In a cell line derived from Danio rerio gill tissue, NIC treatment (3–7 mg/L for 12 h) has been shown to induce intracellular ROS generation in a dose-dependent manner [ 100 ].…”
Section: Resultsmentioning
confidence: 99%
“…Oxidative stress causes significant damage that accelerates cellular aging. This aging process leads to serious pathologies such as cancer, cardiovascular disease, diabetes, neurodegenerative disease, inflammation, digestive diseases, and metabolic syndrome [ 1 3 ]. Several situations in daily life lead to the production of free radicals responsible for oxidative stress.…”
Section: Introductionmentioning
confidence: 99%